2017
DOI: 10.1007/s00248-017-1036-5
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between a Bacterivorous Ciliate Aspidisca cicada and a Rotifer Lecane inermis: Doozers and Fraggles in Aquatic Flocs

Abstract: Activated sludge is a semi-natural habitat composed of macroaggregates made by flocculating bacteria and inhabited by numerous protozoans and metazoans, creating a complicated interactome. The activated sludge resembles the biological formation of naturally occurring floc habitats, such as Bmarine snow.^So far, these two types of habitat have been analyzed separately, despite their similarities. We examined the effect of a bacterivorous ciliate, Aspidisca cicada, on the quality of the macroaggregate ecosystem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Such a setup allowed simulation of wastewater treatment process (SBR) with all phases involved. Activated sludge originating from WWTP created the habitat much more complicated than that of experiments described by Walczyńska and coauthors (2018), where only A. cicada and Lecane rotifers were used. In this research, the clear differences in floc area between control and experimental vessels probably resulted from the fact that control was maintained Aspidisca‐free throughout the experiment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a setup allowed simulation of wastewater treatment process (SBR) with all phases involved. Activated sludge originating from WWTP created the habitat much more complicated than that of experiments described by Walczyńska and coauthors (2018), where only A. cicada and Lecane rotifers were used. In this research, the clear differences in floc area between control and experimental vessels probably resulted from the fact that control was maintained Aspidisca‐free throughout the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…The role of ciliates in processes of the bacterial macroaggregates formation in natural water habitats and wastewater treatment plants was the subject of several research (Curds, 1963;Arregui et al, 2007Arregui et al, , 2008. Recent studies by Walczyńska et al (2018) showed that A. cicada significantly influences the size and structure of freshly created flocs. These results remain in contradiction to our current results showing that addition of dense culture of A. cicada did not have a statistically significant effect on the area and compactness of flocs.…”
Section: Flocs Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial densities of rotifers (which were same for each clone) planted at the beginning of experimental parts were 110, 120 and 250 indiv/mL for MH, SHT and SHO2 stages, respectively. This number was far below the population carrying capacity because L. inermis rotifers may reach densities as high as tens of thousands per mL (45 000 indiv/mL was reported by Walczyńska et al, 2017). The rotifers in each cage were fed 200 µL of commercial bioproduct Bio-Trakt®, which has been successfully used in L. inermis mass culture previously (Fialkowska et al, 2019).…”
Section: Methodsmentioning
confidence: 92%
“…They have been elucidated as biomarkers for improved environmental quality, such as in the soil (Abraham et al, 2019). Moreover, some species actively reduce bacterial flocs and increase ammonia removal from activated sludge, leading to a long-term enhancement of sewage-treatment through activated sludge (Walczyńska et al, 2018). Also, they are key aquatic biosensors towards heavy metals due to the absence of a rigid cell wall, exhibiting in many cases the loss in cells´ morphological integrity; roundness, intracellular vacuolization, morphological deformities and cellular rupture (Pudpong andChantangsi, 2015 andMadoni andRomeo, 2006;Somasundaram et al, 2018).…”
Section: Introductionmentioning
confidence: 99%